1989
DOI: 10.1111/j.1365-2133.1989.tb15509.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of factor XIIIa positive dermal dendritic cells in normal and inflamed skin

Abstract: The immunocytochemical identification and characterization of indigenous dermal dendritic cells (dermal dendrocytes) using a rabbit polyclonal antibody to clotting enzyme factor XIII subunit A (FXIIIa) was carried out on normal and inflamed human cutaneous tissue. The immunophenotype of FXIIIa positive dendritic cells was analysed with a panel of 18 monoclonal antibodies using immunoperoxidase and double immunofluorescence staining techniques. The antibody against FXIIIa detected highly dendritic dermal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
210
1
17

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(235 citation statements)
references
References 35 publications
7
210
1
17
Order By: Relevance
“…In 1986, Nemes & Thomazy reported that 'histiocytic reticulum cells' of human lymph nodes expressed factor XIIIa [41]. Using MoAbs, others have subsequently shown that factor XIIIa + cells may express macrophage antigens [42][43][44]. Nickoloff & Griffiths further stressed the importance of factor XIIIa-expressing dendrocytes in implying that they might have a significant role in the pathogenesis of AIDS-related Kaposi's sarcoma [45].…”
Section: Dendrocyte Confusionmentioning
confidence: 99%
“…In 1986, Nemes & Thomazy reported that 'histiocytic reticulum cells' of human lymph nodes expressed factor XIIIa [41]. Using MoAbs, others have subsequently shown that factor XIIIa + cells may express macrophage antigens [42][43][44]. Nickoloff & Griffiths further stressed the importance of factor XIIIa-expressing dendrocytes in implying that they might have a significant role in the pathogenesis of AIDS-related Kaposi's sarcoma [45].…”
Section: Dendrocyte Confusionmentioning
confidence: 99%
“…8 Os dendrócitos dérmicos são observados na derme normal, podendo haver aumento dessas célu-las em doenças inflamatórias e tumorais, mas não há consenso sobre seu papel nos mecanismos que ocorrem durante os períodos de exacerbação e de acalmia das lesões de psoríase. 9,10 São identificados pela positividade a diferentes marcadores. O FXIIIa, bem caracterizado por Cerio e cols., 10 mostra-se como um bom marcador.…”
Section: Introductionunclassified
“…Especula-se a semelhança entre elas e as LC (CD1a+ DR+). 9,10 Os dendrócitos dérmicos vistos à microscopia eletrônica mostram abas membranosas (dendritos citoplasmáticos finos e alongados) que se dispõem ao redor da parede dos vasos. Naqueles localizados logo abaixo da epiderme (dendrócitos subepidérmicos), a aba se apresenta paralela à junção dermoepidérmica.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Um outro grupo de células dendríticas da pele são os dendrócitos dérmicos (DD) Fator XIIIa+ (DD FXIIIa+), que possuem funções de fagocitose e apresentação de antígenos (Cerio et al, 1989;Pagliari e Sotto, 2002;Sotto et al, 2004). A presença desses DD FXIIIa+ tem sido relatada nas lesões de SK associado ou não à infecção pelo HIV (Nickoloff e Griffiths, 1989a; Kanitakis e Roca-Miralles, 1992).…”
Section: Introductionunclassified